Correction: Authentication of Allium ulleungense, A. microdictyon and A. ochotense based on super-barcoding of plastid genome and 45S nrDNA - Lee, Minyoung; Lee, Hyo Young; Kang, Jong-Soo; Lee, Hyeji; Park, Ki-Jin; Park, Jee Young; Yang, Tae-Jin (PLOS ONE, 2024)
null